Cellular Therapy in the Treatment of Musculoskeletal Disorders - BanitО. V. (Transplantation and artificial organs, 2021)
The number of injuries and diseases of the musculoskeletal system is constantly increasing every year. Given the world’s population aging, more and more attention is paid to disease prevention and the development of specific treatment options. Recently, there has been a dynamic growth of cell technology. The aim. To evaluate the safety and effectiveness of cell-based medicinal products from adipose tissue for the treatment of musculoskeletal disorders and compare them with each other. Materials and methods. In 2018-2020, at the premises of the Department of Traumatology and Orthopedics of Zaporizhia Medical Academy of Post-Graduate Education of the Ministry of Health of Ukraine and the Department of Orthopedics, Aesthetic and Regenerative Medicine of Vitacenter General Hospital, 45 patients with orthopedic disorders were treated using cell-based medicinal products made from native adipose tissue. In 40 cases, stromal-vascular fraction obtained from native adipose tissue using various devices (Goisis, Regenlab, Arthrex SVF, Lipogems®) was injected. Five patients were treated with cultured autologous chondrocytes and multipotent mesenchymal stromal cells from adipose tissue obtained in collaboration with a specialized laboratory “Ilaya.regeneration”, Kyiv. Results and discussion. In the first group, 4 patients had no adverse reactions, only one patient after administration had manifestations of gonarthritis with subsequent improvement. No patients had adverse reactions to the introduction of stromal-vascular fraction. Patientsof both groups were observed for 3-5 days after the procedure, and then once a month; the assessment was performed using VAS, IKDC, WOMAC, KOOS, KSS. All the patients showed gradual decrease in pain improved joint function, and improved quality of life. It is probably incorrect to compare these groups in terms of the number of patients, but we saw a similar pattern in clinical manifestations in both groups. Our observations showed a difference only in the duration of positive changes noted by patients. In the group of patients who received cellbased medicinal product from the stromal-vascular fraction, the positive effect gradually decreased within 1.5-2 years. After the introduction of cultured cell-based products in patients, their clinical condition improved to a level that was maintained for 3 years without significant changes